Notes to Philosophy 167: Class 3 -- Kepler's Astronomia Nova: The Orbit of Mars -- Part 3. - Smith, George E. (George Edwin), 1938- (Tufts Archival Research Center, 2015)
Synopsis: Kepler's Response in Astronomia Nova -- The Empirical Problem of Determining an Orbit.; Generally corresponds to the video segment: Class 3, Part 3.